A Tale of Two Waves: Changes in the Use of Noninvasive Ventilation and Prone Positioning in Critical Care Management of Coronavirus Disease 2019. (3rd December 2021) - Parker, Alexander J.; Mishra, Monalisa; Tiwary, Pooja; Sharman, Mike; Priya-Sharma, Manu; Duncan, Alastair; Shanmugam, Mohan; Bhatia, Kailash; Fullwood, Catherine; Martin, Andrew D.; Wilson, Anthony
Abstract : Supplemental Digital Content is available in the text. Abstract : Importance: New treatments and increased experience are changing the management of hospitalized coronavirus disease 2019 patients but the impact on ICU management is unclear. Objectives: To examine characteristics, ventilatory management, and outcomes of critically ill patients in two distinct waves of the pandemic. Design, Setting, and Participants: Observational cohort study in an ICU in a single-center university-affiliated U.K. hospital. Two-hundred ten adults with coronavirus disease 2019 admitted to ICU between March 17, 2020, to May 31, 2020, and September 1, 2020, to December 10, 2020, with hourly data and 100% follow-up to ICU discharge. Main Outcomes and Measures: Data were extracted from the electronic medical record for patient characteristics and clinical data. Patients were classified into distinct waves of the pandemic and assessed for differences between the two waves. Results: The duration of noninvasive ventilation/nasal high flow increased in wave 2 versus wave 1, both in self-ventilating patients (107 vs 72 hr; p = 0.02), and in those ultimately requiring invasive mechanical ventilation (34 vs 10 hr; p = 0.02). The proportion of survivors treated without invasive mechanical ventilation increased in wave 2 (59% vs 39%; p = 0.01). In both waves, longer duration of noninvasive ventilation/nasal high flow prior to intubation was associated with higher ICU mortality (survivors 10 hr [4–21 hr] vs nonsurvivors 50 hr [23–124 hr]; p < 0.01). Proned invasive mechanical ventilation was common (54.7%) and prolonged. In wave 2, invasive mechanical ventilation patients were generally more hypoxic with proning initiated at lower Pao2 /Fio2 ratios (81 vs 116 mm Hg; p = 0.02) and yielding smaller improvements in Fio2 requirements. Continued proning episodes despite poor responses were commonplace and typically futile. Length of stay for patients requiring tracheostomy increased markedly in wave 2 (51.3 vs 33.7 d; p = 0.03). Overall survival remained similar in wave 2 (68.0% vs 60.9%; p = 0.31). Conclusions and Relevance: Our data suggest that management of critically ill coronavirus disease 2019 patients is changing with more survivors avoiding invasive mechanical ventilation. Duration of noninvasive ventilation/nasal high flow use is increasing, which may be associated with worsening outcomes for individuals who require invasive mechanical ventilation. Among invasively ventilated patients, changes in the use of and response to prone positioning and increased length of stay following tracheostomy may imply that the care of these patients is becoming more challenging.